Shining leaf chafers (Scarabaeidae: Rutelinae) and rhino beetles (Scarabaeidae: Dynastinae) of the Macau SAR, China. (3rd April 2023) - Perissinotto, Renzo; Lu, Yuan-Yuan
ABSTRACT: Recent observations and a review of historical collections and literature have revealed that the diversity of scarab beetles in the Macau Special Administrative Region (SAR) of South China is substantially higher than previously reported. In this latest account, nine identified species are reported from this area in the Rutelinae subfamily, within the genera Adoretus, Anomala, Mimela, Pseudosinghala and Popillia . The subfamily Dynastinae appears to be locally represented by two species within the complex oriental genus Xylotrupes and the more widespread genus Alissonotum, respectively. With the exception of A. rubripes rubripes, P. mutans and X. siamensis, which are observed regularly and in reasonable numbers, all the other species are recorded very infrequently and often as single individuals. Thus, while the biodiversity potential of the region is relatively high, most species appear to be under threat of local extinction. This can be attributed mainly to the rapid habitat degradation, use of pesticides and extreme light pollution that are currently occurring in this SAR.